2015
DOI: 10.1007/s13280-015-0682-4
|View full text |Cite
|
Sign up to set email alerts
|

Valuation of ecotoxicological impacts from tributyltin based on a quantitative environmental assessment framework

Abstract: In the scientific literature, few valuations of biodiversity and ecosystem services following the impacts of toxicity are available, hampered by the lack of ecotoxicological documentation. Here, tributyltin is used to conduct a contingent valuation study as well as costbenefit analysis (CBA) of measures for improving the environmental status in Swedish coastal waters of the Baltic Sea. Benefits considering different dimensions when assessing environmental status are highlighted and a quantitative environmental… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…Due to the lack of integrated global marine status assessments that incorporate economic and social aspects [32], the cost of not restricting scrubber water discharge was limited to the Baltic Sea Area and includes only the aspect of marine ecotoxicity damage cost based on WTP studies [9,29,30]. On a Baltic Sea level, the monetary gain of the scrubber eet, by not switching to more expensive fuels, could be put in relation to the societal damage cost that their choice of installing scrubbers have on the marine environment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to the lack of integrated global marine status assessments that incorporate economic and social aspects [32], the cost of not restricting scrubber water discharge was limited to the Baltic Sea Area and includes only the aspect of marine ecotoxicity damage cost based on WTP studies [9,29,30]. On a Baltic Sea level, the monetary gain of the scrubber eet, by not switching to more expensive fuels, could be put in relation to the societal damage cost that their choice of installing scrubbers have on the marine environment.…”
Section: Discussionmentioning
confidence: 99%
“…A selection of the scrubber eet, operating within the Baltic Sea Area, is further assessed with respect to societal damage cost as an example of the cost of not restricting scrubber water discharge. The societal damage cost associated to marine ecotoxicity from scrubber water discharge is estimated by combining results from previous willingness-to-pay (WTP) studies [29,30] with calculated toxicity potentials (from ReCiPe characterization factors [31]) of open and closed loop scrubber water.…”
Section: /Mwh Has Been Reportedmentioning
confidence: 99%
“…For Environmental Prices the impact modelling is based on ReCiPe 2013 between individualist and hierarchist perspectives and the economic valuation is based on the data by Kuik et al [82]. For the Ecovalue method, the values are based on a study by Noring et al [112] on tributyline pollution, but no documentation could be found how the tributylene pollution was transferred to 1,4-DCB equivalents. Even though Noring et al [112] excluded very high answers, the obtained values are the highest.…”
Section: Marine Ecotoxicitymentioning
confidence: 99%
“…For the Ecovalue method, the values are based on a study by Noring et al [112] on tributyline pollution, but no documentation could be found how the tributylene pollution was transferred to 1,4-DCB equivalents. Even though Noring et al [112] excluded very high answers, the obtained values are the highest. The value is based on contingent valuation and WTP that was linked to reaching a certain policy target that would increase the environmental status of several snails and other species.…”
Section: Marine Ecotoxicitymentioning
confidence: 99%
“…No benefits could be estimated for contaminants in the marine environment (D8) and contaminants in seafood (D9) due to a lack of site-specific evidence. The few existing valuation studies on contaminants in the Baltic Sea focus on individual substances, e.g., tributyltin (Noring et al, 2016) or oil (Ahtiainen, 2007;Juntunen et al, 2013). Moreover, the new measures targeting contaminants are related to research activities (measures 30 and 31 in Table 3) thus their contribution to achieving GES by 2020 was assessed to be very low (Oinonen et al, 2016, Table S2).…”
Section: Finnish Marine Waters Of the Baltic Seamentioning
confidence: 99%